Harvesting energy vibration derived from the rotational speed of a A 4-stroke engine - Farezi Andriansyah; Nur Indah; Subekti Subekti (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2024)
The utilization of vibration energy from a 4-stroke engine as a potential source of electrical energy. Previous studies have focused on analyzing the vibration characteristics and frequency response functions of the 4-stroke engine, but there is a lack of research on harnessing vibration energy as a source of electrical energy. Therefore, this research aims to fill this gap by developing a system to harness the vibration energy from the 4-stroke engine, making it a primary focus of the study. The method employed is an experimental study involving data collection using an FFT Analyzer and Matlab. The research results indicate the presence of several mode shapes in the 4-stroke piston motor. The energy harvesting device utilized is of the electromagnetic type. However, the research reveals that the utilization of vibrations from the 4-stroke piston motor as a source of electrical energy is still not efficient and requires further development. There are various mode shapes in the 4-stroke piston motor at different rotational speeds, but the electromagnetic energy harvesting device used is unable to generate significant electrical energy. Therefore, this research provides a foundation for conducting further research in utilizing the vibrations of a 4-stroke piston motor as a more efficient source of electrical energy